2022
DOI: 10.3390/cancers14153607
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Long-Term Aesthetic and 10 Years Oncologic Outcome following Risk-Reducing Mastectomy and Implant-Based Breast Reconstruction with or without Nipple Preservation

Abstract: Incidence of bilateral risk-reducing mastectomies (RRMs) is increasing. The aim of this study was to compare satisfaction, aesthetic and oncological outcomes in women undergoing RRM with implant-based reconstruction comparing nipple-sparing mastectomy (NSM) with skin-sparing mastectomy (SSM) (sacrificing the nipple +/− nipple reconstruction). Women who had undergone bilateral RRM between 1997 and 2016 were invited. Aesthetic outcome and nipple symmetry were evaluated using standardized anthropometric measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This could be due to the tumor in ltrating the nipple or a surgeon-affected impact, although NSM has been proven to be oncologically safe [16,17]. In addition, we could not prove that NSM was associated with fewer complications [21,22]; however, this could be due to higher complication rates in patients with diseased breasts [13]. Similar to previous studies, we did not observe any difference in complication rates between sub-and pre-pectoral implant-based reconstruction [22][23][24][25].…”
Section: Discussionmentioning
confidence: 90%
“…This could be due to the tumor in ltrating the nipple or a surgeon-affected impact, although NSM has been proven to be oncologically safe [16,17]. In addition, we could not prove that NSM was associated with fewer complications [21,22]; however, this could be due to higher complication rates in patients with diseased breasts [13]. Similar to previous studies, we did not observe any difference in complication rates between sub-and pre-pectoral implant-based reconstruction [22][23][24][25].…”
Section: Discussionmentioning
confidence: 90%
“…Postoperative complication occurrence, based on recent studies, is reported to be around 43%, and thus not very far from the postoperative complication rate of breast reconstruction after oncological surgery independent of prophylactic indications, and additional surgery for medical or aesthetic purposes was required in about 72% of cases [ 14 , 15 , 16 ]. However, the current literature shows very promising results related to the long-term aesthetic outcomes of BRRM [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increased use of preventive bilateral mastectomy has expanded the selection of the I-BBR one-stage technique as the preferred reconstructive method ( 60 , 61 ). One reason is that skin sparing mastectomy and nipple sparing mastectomy (SSM/NSM) incisions in the inframammary fold or lateral breast crease favor implant colocation over autologous options, in which access to the recipient’s vessels would be limited ( 62 ).…”
Section: Basic Concepts In Breast Reconstructionmentioning
confidence: 99%